Impact of English proficiency on use of Glasgow Coma Scale in geriatric patients with traumatic brain injury - Veronica Layrisse-Landaeta; Gabriela R Dincheva; Shahenda Khedr; Andrew Geng; Michele Schombs; Kazi Maisha; Steven Y Chao; Chun-Cheng Chen (Trauma Surgery & Acute Care Open)
Background The relationship between English proficiency (EP), Glasgow Coma Scale (GCS) and traumatic brain injury (TBI) is not well characterized. We aimed to understand the impact of limited English proficiency (LEP) on the evaluation and outcomes of TBI.Methods Retrospective comparative study in a single institution of patients aged ⪰65 who presented to the emergency department after a fall with head strike between January 2018 and December 2021. TBI was defined as documented loss of consciousness or intracranial hemorrhage (ICH). Relationships between EP, GCS, and TBI were analyzed with multivariable and propensity score-matched models.Results Of the 2905 included, 1233 (42%) had LEP. Most LEP patients were Asian (60%) while the majority of EP patients were non-Hispanic Caucasians (72%). In a univariate analysis, LEP had higher incidence of decreased GCS and was strongly correlated with risk of TBI (OR 1.47, CI 1.26 to 1.71). After adjusting for multiple covariates including race, LEP did not have a significantly increased risk for GCS score <13 (OR 1.66, CI 0.99 to 2.76) or increased risk of TBI. In the matched analysis, LEP had a small but significantly higher risk of GCS score <13 (OR 1.03, CI 1.02 to 1.05) without an increased risk in TBI. Decreased GCS remained strongly correlated with presence of ICH in LEP patients in the adjusted model (OR 1.39, CI 1.30 to 1.50).Conclusions LEP correlated with lower GCS in geriatric patients with TBI. This association weakened after adjusting for factors like race, suggesting racial disparities may have more influence than language differences. Moreover, GCS remained effective for predicting ICH in LEP individuals, highlighting its value with suitable translation resources.Level of evidence This is a Level III evidence restrospective comparative study.